Make your web site work for you : - Cannon, Jeff (McGraw-Hill, 2000)
You’ll learn to create content that drives consumers to your site and sells products, and how to track and use consumer information to build profits both on- and off-line. "Content is King," advises author Cannon, who presents ten simple steps for developing and managing effective content. Discover how to optimize your site’s "metatags" so that search engines draw the greatest number of contacts. Find out if "micro-sites" placed on other websites will attract more business than a site of your own. And understand how e-mail and electronic newsletters can promote your site economically and efficiently. Written for marketing and advertising professionals as well as entrepreneurs, MAKE YOUR WEBSITE WORK FOR YOU is free of confusing technical jargon. With solid, step-by-step directions, clear illustrated screenshots, dramatic case studies and a complete list of online resources, it’s an invaluable toolbox for creating a dynamic, profitable website of your own.